Sexual violence mitigation in realizing a violence-free campus - Nursyifa, Aulia; Somantri, Gumilar Rusliwa; Ery Seda, Francisia Saveria Sika (International Journal of Public Health Science (IJPHS), 2024)
Sexual violence occurs in higher education institutions. Sexual violence mitigation studies have a theoretical novelty using Giddens' structuring of the problem of sexual violence. The research aims to determine the relationship between policy stakeholders, lecturers, students, and education staff; know the obstacles and challenges; and know the model of sexual violence mitigation in higher education. The research used qualitative with case studies of three higher education in Indonesia. The informant consisted of 27 respondents: students, lecturers, and education staff. Data collection through interviews, documentation, observation, and focus group discussion (FGD). Data processing using the NVivo 12 Plus application; Publish or Perish; and VOSviewer. Data analysis using: data reduction; present data; and conclusion. This research shows that the relationship is very important between policymakers and lecturers, students, and education staff in efforts to prevent and handle sexual violence. Cooperation of all parties in facing challenges in handling and prevention of sexual violence on campuses that have obstacles, to realize a campus free from violence. This study concludes that realizing a campus that is free from sexual violence can be implemented on campuses in Indonesia. Recommendations for participatory and gender-responsive sexual violence mitigation policy models are applied in higher education in Indonesia.